Student Quality Management in Strengthening Al-Islam and Muhammadiyah at SMA Muhammadiyah 1 Taman: Manajemen Mutu Bidang Kesiswaan Dalam Penguatan Al-Islam dan Kemuhammadiyahan di SMA Muhammadiyah 1 Taman - Syaadah, Aminatus (Journal of Islamic and Muhammadiyah Studies, 2020)
This paper discusses the importance of implementing quality management in student's field in strengthening Al-Islam and Kemuhammadiyahan. The quality of education is one of the benchmarks of the success of an educational process in school. This process starts from the input (input), the process (teaching and learning activities), to the output (graduates). The quality of education can be interpreted as the ability of school to manage operationally the components related to school, so as to produce added value to these components according to standard norms or general standard. Student sector is one of the important component in the management of education quality. This research is a qualitative-descriptive research which is expected to be able to uncover various infor- mation with a careful and meaningful description-analysis. Sources of data in this study include the principal, student vice principal, Al-Islam teacher and Kemuhammadiyahan teacher. Data collection is done by interview, observation, and documentation. As for the data analysis techniques through the stages of data reduction, data presentation and data analysis. The results of the study include (a) quality management in the field of stu- dent implemented based on the values of Al-Islam and Kemuhammadiyahan. (b) Islamic and Kemuhammdiyahan values are the quality standards of the student field.